INTEGRASI KONTEKS PENDIDIKAN AGAMA KRISTEN KEDALAM PELAKSANAAN PEMBELAJARAN - Lisna Novalia (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2020)
Any education will always pay attention to the context. Likewise the Christian Religious Education cannot be separated from its context. The context which is always related to the principles and practices of Christian Religious Education is the family, church and school context. These three contexts have their own characteristics but they all lead to how Christian Religious Education can be carried out well and provide positive and good influence and results. This research emphasizes that Christian Religious Education practitioners always pay attention to the context in which Christian Religious Education is carried out. The method used in this research is library research with the intention of collecting various information or data from various sources, the data is processed and analyzed and conclusions are given. The findings of this study that the Christian Religious Education implemented cannot be separated from the context of the family, church and school.